The impact of the long tail economy on the business result of the digital platform: The case of spotify and match group - Joško Lozić; Marin Milković; Katerina Fotova Čiković (UTMS Journal of Economics, 2022)
Purpose: The aim of this paper is to analyse the business performance of corporations from the platform economy model in the context of the long tail economy model. By comparing business results, analyse the significance of the impact of the long tail economy on business performance. Methodology: The research is focused on analysing the business results of Spotify and Match Group corporations. The research compares the business results of selected corporations in the context of the impact of long tail on business management, financial result and the trend in the number of users of the platform. The methodological framework is unique and applicable to all other corporations from the platform economy model. Results: The survey results showed significant differences in the impact of the long-tail economy on selected corporations. In addition, the survey results showed a significant impact of other factors on the business result that are not closely related to the long-tail economy. Conclusion: The effects of the long-tail economy model need to be analysed on a case-by-case basis in the platform economy. Both corporations are increasing total revenue and customer numbers, but Spotify is operating at a loss, while Match Group is increasing profits year on year.
Keywords: O31; O33; 330; Gross profit; long tail economy; long tail business models; Match Group; platform economy; Spotify